Design and Development of Automation System for Measurement of Flow Nozzle Robot Spray Based on Programmable Logic Controller and Human Machine Interface at PT ADM Casting Plant - Joko Purwanto; Karya Suhada; Rukmanta Jayawiguna; Aprilia Hananto; Aviv Yuniar Rahman (Universitas Singaperbangsa Karawang, 2020)
The spray is one of the important processes in the metal smelting industry that uses die casting machines to make aluminium products. This spraying process serves to prevent the problem of stamps (products attached to the dies/mold) due to overheating (overheating) on ​​the surface of the dies. The main device in this spraying process is the nozzle that is driven by a coil from the solenoid valve. To maintain the quality of the output spray to remain standard, routine maintenance is carried out manually by two operators. Operator one is outside the machine area to see the digital flow sensor display and the second operator is inside the machine area to operate the solenoid valve nozzle spray. Communication between operators plays an important role when carrying out the process of flow spray measurement. This treatment takes 7 hours. The problems found are the lack of security for operators inside the engine area due to the potential for accidents, inaccurate measurements because there is always a pause when communicating between operators inside and outside the engine area and inefficient maintenance time. The purpose of this study is to make a flow nozzle spray measurement system that is safe, accurate, and efficient. This research method uses literature and descriptive methods. The design of this system is done by creating a new display that contains a measurement menu and a record of flow spray measurement data through a Human Machine Interface (HMI) device in the form of an NS-8 Series Omron touch screen that is integrated with a Q-Series Programmable Logic Controller (PLC) type device. Mitsubishi as a controller. From the results of this study, it can be concluded that the flow nozzle spray measurement system display is safer and displays accurate and efficient measurement results because the measurement process is carried out automatically and is operated by one operator outside the machine area.